Strategies to Enhance The Global Competitiveness of MSMEs Through E-Catalogs - Andriyani, Fitriya; Pinandita, Candra Pramula; Oktaviani, Siska Aprilia; Ardhiarisca, Oryza; Pratiwi, Berlina Yudha (Politeknik Negeri Semarang, 2025)
MSMEs have a strategic role in the Indonesian economy, but face various challenges in competing in the global market, such as limited access to capital, low technology adoption, and obstacles in managing digital platforms such as e-catalogs. E-catalogs are a potential solution to expand markets and increase product exposure globally. This research aims to formulate an effective strategy in increasing the global competitiveness of MSMEs through the use of e-catalogs, with a case study on CV. Mutiara Sinar Mandiri. This research uses a qualitative approach with a case study method, involving in-depth interviews and secondary data analysis. The research results show that the strategies adopted by CV Mutiara Sinar Mandiri, such as the use of e-catalogs and a proactive marketing approach, have provided positive results, but there is still room for improvement in terms of relations with the government and increasing competitiveness in the global market. A more collaborative and innovative approach is needed to maximize the potential of companies in the government procurement market. It is hoped that this research can provide practical recommendations for MSMEs in utilizing e-catalogs to increase global competitiveness and expand international market reach. Keywords: CV. Mutiara Sinar Mandiri, MSMEs, E-catalog, Digitalization, Marketing Strategy, Global Competitiveness, SWOT Analysis